2016
DOI: 10.1002/acn3.321
|View full text |Cite
|
Sign up to set email alerts
|

α‐synuclein conformational antibodies fused to penetratin are effective in models of Lewy body disease

Abstract: ObjectiveProgressive accumulation of α‐synuclein (α‐syn) has been associated with Parkinson's disease (PD) and Dementia with Lewy body (DLB). The mechanisms through which α‐syn leads to neurodegeneration are not completely clear; however, the formation of various oligomeric species have been proposed to play a role. Antibody therapy has shown effectiveness at reducing α‐syn accumulation in the central nervous system (CNS); however, most of these studies have been conducted utilizing antibodies that recognize b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…These results are in agreement with our recent studies utilizing brain penetrant single chain antibodies that showed that clones capable of detecting α-syn oligomers were more effective at reducing synucleinopathy in tg when compared to single chain antibodies that had higher affinity for α-syn monomers (Spencer et al, 2014; Spencer et al, 2016). The advantage of the single chain antibodies in this study was the specificity and the ability to cross the blood brain barrier and as such they represent an important proof of principle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with our recent studies utilizing brain penetrant single chain antibodies that showed that clones capable of detecting α-syn oligomers were more effective at reducing synucleinopathy in tg when compared to single chain antibodies that had higher affinity for α-syn monomers (Spencer et al, 2014; Spencer et al, 2016). The advantage of the single chain antibodies in this study was the specificity and the ability to cross the blood brain barrier and as such they represent an important proof of principle.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we developed single chain antibodies targeting α-syn oligomers and fibrils expressed from lentiviral vectors (Price et al, 2016; Spencer et al, 2014; Spencer et al, 2016). Although promising, there were some limitations, which led to the development of highly specific monoclonal antibodies differentially targeting oligomers versus fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that scFvs against alpha-synuclein variants associated with Parkinson’s disease have excellent therapeutic value [49, 50]. In a similar fashion, since our scFvs selectively bind ALS associated variants of TDP-43, in addition to diagnostic value, the scFvs may also have potential therapeutic value.…”
Section: Discussionmentioning
confidence: 61%
“…Gaining access to the brain with these large molecules is a potential limiting factor, particularly with passive immunization, and the clinical development program is further hindered because target validation is not currently possible. Methods to facilitate brain entry are currently being explored including the use of single‐chain antibodies that can be combined with a fusion protein . Other issues include the risks of inflammation, autoimmune reactions, and accelerating the disease process by inadvertently targeting α‐synuclein species that might be protective rather than toxic …”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Methods to facilitate brain entry are currently being explored including the use of single-chain antibodies that can be combined with a fusion protein. 32,33 Other issues include the risks of inflammation, autoimmune reactions, and accelerating the disease process by inadvertently targeting a-synuclein species that might be protective rather than toxic. 34 2.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%